Perilaku Knowledge Sharing: Anteseden dan Pengaruhnya Terhadap Kemampuan Inovasi Individual - Ninik Probosari; Herlina Dyah Kuswanti (Jurnal Manajemen Bisnis, 2014)
Purpose of this research was to analyze effects of organizational climate, organizational citizenship behavior, and social capital on knowledge sharing behavior. This research also analyzed effect of knowledge sharing behavior on individual innovation capability. Sample was 58 employees of BPR. Data was taken using questionnaires and analyzed using path analysis of linear regression. Result showed that only organizational climate and social capital affected knowledge sharing behavior. Result also showed that knowledge sharing behavior affected individual innovation capability.